REGRESSION ANALYSIS FOR PREDICTING THE DURATION DEPENDENT RESPONSE OF OXIDATIVE STRESS DYNAMICS AND NUCLEAR ANOMALIES IN CATLA CATLA EXPOSED TO CHLORPYRIFOS AND ENDOSULFAN - H. Naz1; S. Abdullah; T. Ahmed3; K. Abbas; M. U. Ijaz (Journal of Animal and Plant Sciences, 2021)
In present work, a statistical model called linear regression was applied to find out the casual relation between the dependent variables oxidative stress dynamics viz. Superoxide dismutase (SOD), peroxidase (POx), catalase (CAT) and glutathion S-transferase (GST) and nuclear abnormalities (NAs) in Catla catla and one independent variable exposure durations of endosulfan and chlorpyrifos (insecticides). Fish were kept under acute toxicity of insecticides mixture for 1-, 2-, 3- and 4-days. The increased SOD activity in organs of fish showed the significant and positive dependence with duration of exposure. CAT activity in gills, liver and kidney showed significantly positive relation while brain, heart and muscle tissues had significantly negative dependence with duration which showed that it decreased with increasing exposure time. The activity of POx in gills, brain and heart showed a significant dependence on exposure duration while liver, kidney and muscle had non-significant dependence with exposure time. The GST activity of fish had highly significant positive relation with exposure time. The SOD, POx and GST activities augmented in organs of fish due to mixture exposure. However, CAT activity induced in kidney, liver and gills of fish while it was decreased in heart, brain and muscles tissues. The results of geno-toxicity showed that MN (micro-nuclei) and NN had significantly positive relation with duration while other NAs had non-significant relation with time exposure. Insecticides mixture exposure increased the formation of MN and NAs in RBCs of experimental group in comparison to control group.
Keywords: Fish; Antioxidant enzymes; genotoxicity; tissues; insecticides